Analysis of Leonardo Edwin Bold Identity: Analisis Identitas Daring Leonardo Edwin - Firdaus, Muhammad Rizal; Agustin , Anggi Tri; Febriana, Poppy (Procedia of Social Sciences and Humanities, 2025)
This study examines the use of code-switching and code-mixing in the YouTube videos of Leonardo Edwin, an Indonesian content creator. As an international student, Leonardo often combines Indonesian and English in his content to reach a wider audience. Using a symbolic interaction theory approach, this study investigates how the interaction between Leonardo and his followers through comments and content affects the image he presents. The results of the analysis show that external code-switching is more common, with the use of English when interacting with international friends. This research is expected to contribute to previous research on the phenomenon of code-switching and code-mixing on social media. Highlights: Audience Engagement – Leonardo Edwin uses code-switching to connect with both Indonesian and international audiences, making his content more inclusive. Symbolic Interaction – His language choices shape his online persona, influenced by interactions with followers and content themes. Predominant Pattern – External code-switching is more frequent, especially when engaging with international friends, highlighting social adaptation in digital communication. Keywords: Social Media, New Media, Youtube, Leonardo Edwin